Analisis Implementasi dan Efektivitas Program Mitigasi di LEMIGAS Tahun 2023 - Hutasoit, Sahala; Yuwono, Minto; Susilowati, Etty (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The oil and gas industry is a critical sector in Indonesia, with LEMIGAS (Research and Development Center for Oil and Gas Technology) playing a significant role in ensuring operational efficiency and safety. This study aims to analyze the implementation and effectiveness of LEMIGAS's mitigation programs in 2023. The research employs a descriptive quantitative method with a case study approach, focusing on high-risk projects within LEMIGAS. Data were collected through in-depth interviews, questionnaires, and document analysis, and analyzed using a risk matrix to evaluate both inherent and residual risks. The study identified eleven main risks, categorized into acceptance and operational risks, including issues like delayed project completion and quality discrepancies. Mitigation measures such as equipment revitalization, coordination, and intensive monitoring significantly reduced the risk levels. For instance, the inherent risk score for revenue acceptance (R1) decreased from 10 to a residual score of 4 after mitigation efforts. Overall, the findings indicate that the structured risk management approach at LEMIGAS effectively reduces the impact and likelihood of risks, ensuring smoother project execution and achievement of organizational goals. Continuous monitoring and periodic evaluations are essential for maintaining effective risk management.